2010
DOI: 10.1097/mao.0b013e3181ca843d
|View full text |Cite
|
Sign up to set email alerts
|

Corticosteroids in the Treatment of Vestibular Neuritis

Abstract: The present systematic review and meta-analysis, based on the currently available evidence, suggests that corticosteroids improve only the caloric extent and recovery of canal paresis of patients with vestibular neuritis. At present, clinical recovery does not seem be better in patients receiving corticosteroids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
43
2
7

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(55 citation statements)
references
References 35 publications
3
43
2
7
Order By: Relevance
“…5). 45 These findings are supported by both a meta-analysis 46 and an observational study. 47 A more recent single-blinded trial that compared corticosteroids to vestibular exercises in acute unilateral vestibulopathy found that vestibular exercises are as effective as treatment with corticosteroids in clinical, caloric, and otolith recovery 48 ; corticosteroid therapy seems to enhance earlier complete acute unilateral vestibulopathy resolution, with no added benefit in the long-term clinical prognosis.…”
Section: Causative Treatmentmentioning
confidence: 72%
See 1 more Smart Citation
“…5). 45 These findings are supported by both a meta-analysis 46 and an observational study. 47 A more recent single-blinded trial that compared corticosteroids to vestibular exercises in acute unilateral vestibulopathy found that vestibular exercises are as effective as treatment with corticosteroids in clinical, caloric, and otolith recovery 48 ; corticosteroid therapy seems to enhance earlier complete acute unilateral vestibulopathy resolution, with no added benefit in the long-term clinical prognosis.…”
Section: Causative Treatmentmentioning
confidence: 72%
“…A clinically relevant vestibular paresis was defined as greater than 25% asymmetry between the right-sided and the left-sided responses. 50 findings, a Cochrane analysis 49 and a meta-analysis 46 make no general treatment recommendation for corticosteroids; they may improve only the recovery of canal paresis, 46 and their effects on life quality have not yet been investigated sufficiently. Thus, further randomized controlled trials are necessary.…”
Section: Causative Treatmentmentioning
confidence: 99%
“…Indeed, both a systematic review [13] and later a Cochrane review of four trials found no significant difference between corticosteroid and placebo in the symptomatic recovery of vestibular function [11], but only one study had assessed symptom recovery [20], and this was not a primary study outcome. The short follow-up period in our study does not make the results with those of Shupak et al [20] directly comparable, but one possibility is that the reduction in acute dizziness symptoms was related to the psychotropic effects of glucocorticoids [8] in our treatment group.…”
Section: Discussionmentioning
confidence: 99%
“…For vestibular neuritis (27), and more so in Bell´s palsy (28), corticosteroids tested in RCT's have recently been shown to exert a beneficial effect. These diseases are the other two idiopathic conditions causing harm to the neurological tissue within the inner ear canal.…”
Section: Discussionmentioning
confidence: 99%